Clinical presentation in insulinoma predicts histopathological tumour characteristics. (16th April 2015) - Wolf, Peter; Winhofer, Yvonne; Smajis, Sabina; Anderwald, Christian‐Heinz; Scheuba, Christian; Niederle, Bruno; Gessl, Alois; Luger, Anton; Krebs, Michael; Koperek, Oskar
Summary Background Insulinomas are rare neuroendocrine tumours (NETs) of the pancreas, characterized clinically by neuroglycopenic symptoms during periods of substrate deficiency. The gold standard test for diagnosing an insulinoma is a 72‐h fast. However, the prognostic value of parameters in the standardized 72‐h fast on histopathological tumour criteria and clinical presentation has not been examined. Methods In thirty‐three patients diagnosed with an insulinoma records, and data were investigated retrospectively. Histopathological tumour characteristics, including staging, grading and size, were reviewed. Grading was performed using Ki‐67 index. Cut‐off values for classical grading (Gclas) were set at G1clas≤2%, G2clas3–20% & G3clas>20% and for modified grading (Gmod) at G1mod<5%, G2mod5–20% & G3mod>20%. Results When Gmod criteria were applied, the initial blood glucose was lower in GII/IIImod patients compared to GImod (2·8 ± 0·8 vs 3·8 ± 1·3 mmol/l; P = 0·046). Basal and end of fast levels of insulin (basal insulin 71 ± 61 vs 20 ± 16 mU/l; P < 0·001; end of fast insulin 77 ± 51 vs 21 ± 20 mU/l; P < 0·001) and c‐peptide (basal c‐peptide 5·4 ± 2·4 vs 2·7 ± 1·6 μg/l; P = 0·004; end of fast c‐peptide 5·3 ± 2·4 vs 2·5 ± 1·4 μg/l; P = 0·001) were significantly higher in GII/IIImod than in GImod. No differences between the groups were observed when Gclas criteria were applied. Additionally, close correlations were observed between insulin concentration, Ki‐67 index and tumour size. Conclusion This study shows an impact of histopathological tumour characteristics in patients suffering from an insulinoma on clinical presentation during a standardized 72‐h fast. Lower initial blood glucose levels and higher concentrations of insulin and c‐peptide are associated with worse tumour grading and larger tumour size.